Imagining Globalization
XI, 256 p.
Keywords: This collection gives voice to the peoples and groups impacted by globalization as they seek to negotiate their identities, language use, and territorial boundaries within a larger global context. Rather than viewing globalization as one-dimensional (i.e., cultural, economic, or political), the approaches taken by the authors reflect a nuanced and multifaceted discussion of globalization that integrates all three perspectives. They explore identity, boundaries, language use, and other issues in the context of specific temporal and spatial contexts.